2020
DOI: 10.1002/advs.201902868
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Effects of Hydrolysis‐Derived DMAI/DMAPbIx Intermediate Compound on the Performance of CsPbI3 Solar Cells

Abstract: Introducing hydroiodic acid (HI) as a hydrolysis‐derived precursor of the intermediate compounds has become an increasingly important issue for fabricating high quality and stable CsPbI3 perovskite solar cells (PSCs). However, the materials composition of the intermediate compounds and their effects on the device performance remain unclear. Here, a series of high‐quality intermediate compounds are prepared and it is shown that they consist of DMAI/DMAPbIx. Further characterization of the products show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 62 publications
1
58
0
Order By: Relevance
“…3D perovskites generally have the chemical formula ABX 3 . Figure 1a shows six X-position atoms forming an octahedral structure, where B-position atoms are located at the center of the octahedron, with [BX 6 ] 4− octahedrons corner-sharing with each other and the A cation occupying the voids made by the anionic framework.…”
Section: Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…3D perovskites generally have the chemical formula ABX 3 . Figure 1a shows six X-position atoms forming an octahedral structure, where B-position atoms are located at the center of the octahedron, with [BX 6 ] 4− octahedrons corner-sharing with each other and the A cation occupying the voids made by the anionic framework.…”
Section: Crystal Structurementioning
confidence: 99%
“…Perovskite has attracted significant interest owing to its high light absorption coefficients, long carrier lifetime and, diffusion length, as well as designable composition and characteristics, [1][2][3][4][5][6] for third-generation solar cells. [7][8][9][10][11][12] As a result of intensive research, the power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rapidly risen from the original 3.8% to current 25.2% over the past ten years.…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence mechanism of DMAI residue for device stability was not revealed in this work, which remains investigated deeply in the subsequent research work. Although huge progresses have been achieved on DMAI, inconsistent conclusions were obtained on its role of DMAI as an additive [12,22,117] or dopant, [77,109] which could be ascribed to different annealing temperatures and times along with different amounts of DMAI and preparation condition (e.g., humidity, oxygen, etc. ).…”
Section: Organic Cationsmentioning
confidence: 99%
“…k) XPS spectra of the C 1s and N 1s peaks of syn‐CsPbI 3 film before and after etching 300 s. Reproduced with permission. [ 62 ] Copyright 2020, Wiley‐VCH.…”
Section: Stabilize Structure: Composition Engineeringmentioning
confidence: 99%
“…More recently, compositional and phase evolution during the formation of DMA-derived CsPbI 3 films was carefully studied from different perspectives. [61,62] It has been found that using a precursor combination of DMAI/PbI 2 /CsI, DMAPbI 3 and Cs 4 PbI 6 are formed in the as-spun films and crystallize into a hybrid DMA 0.15 Cs 0.85 PbI 3 perovskite after annealing at 180 C for 15 min in N 2 , showing a 1.67 eV bandgap and superior stability (negligible decay in absorbance after exposed to 70-80% RH for 15 h) (Figure 5f-h). The achieved bandgap is close to previously reported β-CsPbI 3 .…”
Section: A Site Tuningmentioning
confidence: 99%